Efeito do treinamento físico de natação nos ratos espontaneamente hipertensos (SHR) antes, durante e após o desenvolvimento da Hipertensão Arterial - Garcia, Maureen Gabriela Pena [UNIFESP] (2019)
Hypertension is a disease of high prevalence and mortality in the world. Changes in the sympathetic nervous system (SNS) and cellular calcium homeostasis are present in hypertension. In addition, a link was also established between increased SNS activity and inflammation in the pathophysiology of hypertension. The physical training (PT) originates a series of physiological adaptations that influence the cardiovascular system; this physical training is used in hypertensive patients, as non-medicated treatment for the control of blood pressure (BP). The aim of the present study was to study the effect of swimming on sympathetic neurotransmission and cellular calcium homeostasis in chromaffin cells of the adrenal gland (CCA), vas deferens (VD), retroperitoneal adipose tissue and concentration in serum of C reactive protein (CRP) in spontaneously hypertensive rats (SHR) before, during and after development of hypertension. Using normotensive animals (NWR) and SHR aged 8-12-20 weeks divided into three groups: sedentary NWR (NWR-Sed), sedentary SHR (SHR-Sed) and trained SHR (SHR-Tre). We evaluated the effect of swimming in: 1) arterial pressure and heart mass, 2) secretion of catecholamines by CCA and VD. 3) participation of calcium channel dependent voltage (CCDV), in pharmacological and neurogenic contraction and cellular calcium homeostasis, 4) concentrations of calcium present in the intracellular stores of the endo/sarcoplasmic reticulum (RE/RS) and mitochondria (MIT), VD and CCA, 5) retroperitoneal fat amount, 6) serum concentration of C reactive protein (CRP). Compared to SHR-Sed, SHR-Tre: 1) prevented BP increase, and increased heart mass. 2) decreased basal [Ca2+]i and after stimulation with ACh in CCA, 3) decreased catecholamine secretion when CCA were stimulated with Bay K-8644 with CRT and CCCP. 4) reduced twitch neurogenic contraction in the presence of Bay K-8644, CRT and CCCP. 5) reduced the responses of α1 and P2X1 in DD. 6) decreased retroperitoneal fat, and 7) reduced the serum concentration of CRP in all groups of trained animals. Based on the above results we can conclude that the training was able to attenuate the increase in blood pressure and remodeling of the heart mass in SHR-Tre animals. In addition, it produced a reduction of the sympathetic nerve activity evidenced by the reduction of [Ca2+]i, which may have led to a decrease in catecholamine secretion and a decrease in neurogenic contractions, reduced the amount of retroperitoneal fat and CRP concentrations. These data suggest the effectiveness of physical training in preventing the establishment of arterial hypertension as well as its underlying effects in our animal model and reinforce the indication of physical activity as a participant in non-drug treatment of arterial hypertension.